Performance evaluation of a new RT-PCR assay for the screening of carbapenemase-producing enterobacterales (CPE) and Acinetobacter spp. - G. Tocci; V. Lepera; G. Palladini; A. Zappavigna; C. Cordini; C. Gorrini; L. La Vergata; R. Schiavo; G. Lo Cascio (Microbiologia Medica)
Not available.